Therapeutic Management of Snake Bite in a Rottweiler Dog - Bharai, MJ; Dodiya, PG; Vagh, AA (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
M Snakebite cases are more common in horses and dogs when compared to other animals such as cattle, sheep,  and goats. Snake envenomation can be difficult to diagnose if  the incident was not witnessed. Clinical signs may vary greatly  depending on the species of snake involved, and the quantity  and toxicity of the venom injected. Dogs are commonly  presented with extensive edematous swelling, severe pain,  ecchymosis, and discoloration of the skin in the affected area  within several hours after the bite (Garg, 2002) The animals  exhibit various symptoms like cardio-pulmonary dysfunction,  local tissue damage, blood coagulation defects, ataxia etc,  depending on type of snake bite (Bhardwaj, 2011). Systemic  signs can vary and may include hypotension, shock, cardiac  arrhythmias, bleeding disorders, ptyalism, nausea, vomiting,  respiratory distress, mental confusion, rhabdomyolysis,  and acute renal failure (Ananda et al., 2009).
Keywords: Anti-venom serum; Clinical management; Dog; Snakebite